ANALISIS PERSEPSI SISWA TERHADAP FUNGSI HUTAN MANGROVE KARANGSONG SEBAGAI SUMBER BELAJAR GEOGRAFI - Qonita Surayya (Sosio-Didaktika: Social Science Education Journal, 2017)
This research discusses students’ perceptions of the function of Karangsong mangrove forest as a geography learning resource. The students’ perception about the presence of Karangsong mangrove forest as a learning resource is necessary because of the better the students' perceptions of the learning resources used, the more likely the students will get good learning outcomes. This research aims to describe how the students’ perception of the presence of Karangsong mangrove forest as a geography learning resource.This research used quantitative method with descriptive analysis. The population in this research is students of XI class of SMAN 2 Indramayu. The technique of data sampling used in this research is cluster sampling. The selected sample is based on a class with the highest score than the other class, the sample is XI IPS class which consists of 33 students. The instruments used in this research are observation, questionnaire, and documentation. To know the students’ perception, the researcher distributed the questionnaires to the students before and after the learning process in Karangsong mangrove forest.The result of the analysis shows that before the students do the learning process in Karangsong mangrove forest, the average score of the questionnaire belongs to adequate score with a percentage of 60.7%. Yet, after the students do the learning process in Karangsong mangrove forest, the average score of the questionnaire belongs in an excellent category with a percentage of 92.4%. Therefore, based on the calculation with N-Gain, it shows the average of N-Gain in the amount of 0.8% and it belongs to the high category of n-gain. In conclusion, after doing the learning process in karangsong mangrove forest, the students’ perception of the function of Karangsong mangrove forest as a geography learning resource is excellent.